Distribution of the functional groups in various coals with different spontaneous propensity. Issue 6 (2nd June 2020) - Xu, Tao; Shen, Xin-Tao; Chen, Jing-Yi; Chen, Zhi-Hao
ABSTRACT: The distribution of oxygen-containing functional groups, aromatic hydrocarbons, and aliphatic groups in coal with different spontaneous combustion propensity were studied. Adiabatic method was used to determine the spontaneous combustion propensity of six different coal samples. FTIR was used to collect the spectrum of the coal, and the peak areas of the functional groups were analyzed. The proportion of C = C, CH3 /CH2, OH, C = O, COOH, C-O, and C-O-O obtained based on the peak areas was calculated, and the spontaneous combustion propensity was characterized by the distribution of the functional groups. It was found that there is a good corresponding relationship between the content of aromatic functional groups and oxygen-containing functional groups with the self-heating time of the coal samples. The coal with shorter self-heating time has less aromatic groups and more oxygen-containing functional groups. With the increase of the spontaneous combustion propensity of coal, there are less aliphatic hydrocarbons functional groups generally. But among different coal samples, the contents of aliphatic hydrocarbons functional groups differ not great.